Future Perspectives of NMDAR in CNS Disorders - Toni Capó; Joan Biel Rebassa; Iu Raïch; Jaume Lillo; Pau Badia; Gemma Navarro; Irene Reyes-Resina (Molecules)
Neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases are among the leading causes of physical and cognitive disability across the globe. Fifty million people worldwide suffer these diseases, and that number is expected to rise as the population ages. Ictus is another pathology that also courses with neurodegeneration and is a leading cause of mortality and long-term disability in developed countries. Schizophrenia is not as common as other mental disorders, affecting approximately 24 million people worldwide. All these disorders have in common that still there is not an effective pharmacological treatment to cure them. The N-methyl-D-aspartate (NMDA) receptor (NMDAR) has attracted attention as a potential therapeutic target due to its important role in learning and memory and also due to its implication in excitotoxicity processes. Some drugs targeting NMDARs are already being used to treat symptoms of disorders affecting the central nervous system (CNS). Here, we aim to review the implications of NMDAR in these CNS pathologies, its role as a potential therapeutic target, and the future perspectives for developing new treatments focused on these receptors.